Rekonversi Umat Kristen ke Agama Hindu Kaharingan di Kabupaten Pulang Pisau, Kalimantan Tengah - Wayan Gepu; Tardi Edung (Jurnal Penelitian Agama Hindu, 2026)
The shift in the belief system from Christianity to Hinduism actually created a form of consciousness, from individuals who believed in the new faith, then returned to the original teachings. This aspect can be read as a turning point for the occurrence of reconversion in Pulau Pisau Regency. The purpose of this research is to discover the conceptual schema and empirical findings regarding liturgical practices that were initially distracted by the emergence of a new belief (Christianity), then redefined and reconverted to the original teachings (Hindu Kaharingan). This research uses a qualitative method, within a case study approach. The case study (research on the Hindu Kaharingan social-religious community) attempts to investigate a specific case in a specific location. Empirical findings on conversion can be distinguished into 3 factors. First, the main factor leading to a return to the original teachings is self-stimulation or being stimulated by one's own personal will. This can be seen from the imperfect understanding of the new religious system (Christianity), compared to the original religion (Hindu Kaharingan). The second cause is that religious reconversion is caused by amalgamation (mixed marriages). The process of religious reconversion, in its aspect of amalgamation, involves inner changes that occur in Christian communities transitioning to Hindu Kaharingan in Pulang Pisau Regency. Marriage plays an important role in the reconversion process in this area because it involves both endogenous and exogenous origins. The third background is that the reconversion process can be traced back to the legitimacy of the Hindu Kaharingan religion, which is called pandudusan. The ceremony for the return of the righteous person uses 1 coconut, 1 egg, 1 lilis lamiang flower, undus/oil, a bowl of water, tampung tawar, a bowl from the pond, and a knife. In conclusion, religious reconversion involves the accumulation of religious-based authority and the sociological factors of the individual.